1:1 Binary Complexes of Citric Acid with Some Metal Ions: Stability and Thermodynamic Parameters. - SEZA BASTUG†, A.; GÖKTÜRK†, SINEM; SISMANOGLU*, TUBA (Asian Journal of Chemistry, 2010)
This article has been retracted on the request of authors due to the wrong data provided by the authors at the time of submission. We cannot, therefore, vouch for the reliability or integrity of this article.